Organizational Citizenship Behavior of Graduate Trainees in Batticaloa District - Selvarajan, P.; Sreepriya, S. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka., 2021)
The study aims at identifying the Organizational Citizenship Behaviour (OCB) of graduate trainees in Batticaloa District. The literature found many factors which influence the OCB of employees in organizations. However, researchers extracted five factors called Organizational Identification, Job Satisfaction, Task Interdependence, Public Service Motivation and Positive Relationship. The empirical data were collected from 150 graduate trainees in Manmunai North Divisional Secretariat Division in Batticaloa District. A structured questionnaire survey and a few in-depth interviews were conducted to increase the validity of the research. The Statistical Package for Social Sciences (version 26.0) has been used to analyze the data. A reliability test is done to show the reliability of data and the Descriptive statistics, Correlation Analysis and Multiple Regression analysis have been incorporated to get the findings. Further an Independent Samples t-test is carried out to investigate the gender influence in OCB. The findings indicated that job satisfaction,task interdependence, public service motivation and positive relationship are the significantly influencing factors on the OCB of graduate trainees in Batticaloa District. The result of independent samples t-test showed that no significant difference in terms of OCB between male and female graduates. It is concluded that 58.1% of the variance in OCB can be predicted by the above independent variables and 41.9% of the variance would be due to other factors. It is recommended that the policy makers should consider this information in providing the graduate appointments.
Keywords: Graduate trainees; Job satisfaction; Organisational citizenship behavior; Positive relationship; Public service motivation